Diabetes tracking panel: an on-line information system to registration and management - Dixon Salcedo; Albeiro Cortes; Yesid Ternera; Carlos Henriquez; Leidy Martes (Bulletin of Electrical Engineering and Informatics, 2022)
Online hospital information systems enable health care providers to ensure information. Although nowadays there are great technological advances; in Colombia, the impact on the health sector has been low. As a result, there is an increasing deficiency in cities with less access to new technologies. Therefore, it is necessary for the government and health care providers to join efforts to expand the use of information technologies in the health area to improve the overall quality of the service provided. Therefore, this project introduces diabetes tracking panel tests system to improve the management process. The development system is based on several Open-Source platforms, such as MySQL, among others. Finally, we found that implemented system can reduce the time management of diabetes tests by the staff medical and assistance care personal.